Lipid Profiles of College Female Student-Athletes Participating at Different Competition Levels of Organized Sport - Kaila A. Vento; Ferdinand Delgado; Heidi Lynch (Frontiers Media S.A., 2022)
College-aged women are not meeting weekly moderate-to-vigorous physical activity to support lipids protecting against cardiovascular disease onset. Participating in organized sport could assist in physical activity engagement and maintenance while positively impacting lipids predicting cardiovascular disease. However, women may be discouraged from participating in sports if they perceive benefits to be mostly seen at the higher competition levels, thus hindering seeking sports involvement at lesser-intensity levels. A total of N = 78 female athletes participating at the National Collegiate Athletic Association (n = 21), National Junior College Athletic Association (n = 29), and student club (n = 28) completed a personal characteristics questionnaire and provided blood samples to compare physical activity involvement and lipid health profiles. Linear regression modeling was used to assess how the independent variables (i.e., sport level, age, systolic blood pressure, race/ethnicity, sport/physical activity involvement hours per week, and years playing sports) on the dependent variables [i.e., total cholesterol, high density lipid (HDL), and total cholesterol-HDL ratio]. Total sample cholesterol 165.7 ± 34.0, HDL 62.8 ± 15.03, and total cholesterol-HDL ratio 2.8 ± 0.6 were all within a healthy recommendation range, along with per sport level. NJCAA sport level significantly predicted lower total cholesterol, p = 0.043, while identifying as Black significantly predicted higher total cholesterol, p = 0.008. Similarly, identifying as Black significantly predicted higher HDL, p = 0.021. Furthermore, increased systolic blood pressure significantly predicted higher total cholesterol-HDL ratios, p = 0.014. Organized sports participation may help meet physical activity requirements, support healthy lipid profiles, and ward off cardiovascular disease development in female college students regardless of competition level.